2018
DOI: 10.5038/2577-509x.2.2.1019
|View full text |Cite
|
Sign up to set email alerts
|

“I don’t even know where Turkey is.”: Developing intercultural competence through e-pal exchanges

Abstract: Using current events to help preservice teachers understand the world they live in encourages preservice teachers to learn about global issues. It also encourages them to develop skills in analytical thinking and reflective judgment by reading and discussing complex real-life scenarios. A semester-long pen-pal project was crafted to help understand how preservice teachers develop intercultural competence, critical empathy, and become less ethnocentric. Twenty-Six American early childhood preservice teachers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Finally, Black girls are more likely to exhibit fewer disciplinary issues in classrooms that are based on culturally responsive approaches to teaching and learning (Gay, 2018). For this reason, it is critical for teachers to incorporate culturally responsive pedagogies into their classrooms as a means of creating affirming, inclusive, and supportive educational experiences for Black girls (Gay, 2018;Lakhwani, 2019;Lin, 2018;Piquemal et al, 2019). Gay (2018) defines culturally responsive pedagogy as an approach to teaching and learning that uses social and cultural knowledge, language patterns, reference points, and ways-of-being to help students understand and acquire the formal knowledge and skills presented within school curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Black girls are more likely to exhibit fewer disciplinary issues in classrooms that are based on culturally responsive approaches to teaching and learning (Gay, 2018). For this reason, it is critical for teachers to incorporate culturally responsive pedagogies into their classrooms as a means of creating affirming, inclusive, and supportive educational experiences for Black girls (Gay, 2018;Lakhwani, 2019;Lin, 2018;Piquemal et al, 2019). Gay (2018) defines culturally responsive pedagogy as an approach to teaching and learning that uses social and cultural knowledge, language patterns, reference points, and ways-of-being to help students understand and acquire the formal knowledge and skills presented within school curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…As an example of how the SGIS could be employed outside of science, preservice teacher education students in an American midwestern university studying multicultural education were placed in a penpal relationship with counterparts in a Turkish university (Lin, 2018). For 14 weeks the students exchanged information about their everyday lives in each country and the situation resulting from Syrian immigrants escaping their war-torn nation to bordering Turkey.…”
Section: Stage 3: Cooperatementioning
confidence: 99%
“…A bulk of research have been reported on teacher's intercultural language teaching beliefs (Altan, 2018;Arcagök and Yılmaz, 2020;Atay et al, 2009;Beutel and Tangen, 2018;Kaça, 2015;Çetin-Köroğlu, 2016;Çubukçu, 2013;Demircioğlu & Çakır, 2015;Ersoy, 2013;Hayden, Rancic & Thompson, 2000;Israelsson, 2016;Keranen & Bayyurt 2006;Lázár, 2011;Lin, 2018;Oranje and Smith, 2018;Polat & Ogay-Barka, 2014;Sercu, 2005Sercu, , 2006Smolcic & Arends, 2017;Türkyılmaz-Sinclair, 2019;Young and Sachdev, 2011). To start with, Beutel and Tangen (2018) researched the impact of intercultural experiences on shaping pre-service teachers' preparedness to engage with diverse students in Australia and found a positive relationship between the variables.…”
Section: Different Perspectives On Culturementioning
confidence: 99%